KGST . COMECON (Magar Diafilmgyártó Vállalat, 1976)
Produced for the Central Committee of the Hungarian Socialist Workers' Party, Department for Agitation and Propaganda. The film presents the member states and areas of cooperation of COMECON. A film a Kölcsönös Gazdasági Segítség Tanácsa tagországait és az együttműködés területeit mutatja be.